Reflection on Feminist Issues in 2015-2016 in Kim Ji Yeong's Novel, Born 1982 and Lesson Plan - Elvira Azzahra Ramsi; Alfian Rokhmansyah (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to describe: 1) reflection of feminism issues in Cho Nam-Joo's novel Kim Ji Yeong, Born 1982 with a focus on the 2015–2016 setting; 2) the condition of feminism in Indonesia in 2025; 3) relevance and critical reading of feminism issues in Cho Nam-Joo's novel Kim Ji Yeong, Born 1982; 4) components of a comparative literature lesson plan on reflection of feminism issues in Cho Nam-Joo's novel Kim Ji Yeong, Born 1982 with a focus on the 2015–2016 setting. The method used is descriptive qualitative with a literature study approach. The primary data of this study comes from the novel, while secondary data is obtained from articles, journals, and reports related to feminism. The research instrument was developed in the form of an analysis guide based on Simone de Beauvoir's theory. Observation guidelines were used to collect data including in-depth reading, recording, and documentation of secondary sources based on validation with source triangulation and time triangulation techniques as information verification methods. Data analysis used thematic and comparative analysis. Research results: 1) reflection of feminism issues in Cho Nam-Joo's novel Kim Ji Yeong, Born 1982 with a focus on the 2015–2016 setting is gender inequality which is very relevant to the challenges of contemporary feminism, including the issue of Online Gender-Based Violence (KBGO); 2) Indonesia in 2025 shows progress through the enactment of the TPKS Law, increased digital activism, and the expansion of the feminist agenda; 3) the novel remain relevant for reading contemporary feminist phenomena; the domestic burdens, work inequality, and social pressures experienced by the main characters parallel the experiences of Indonesian women; 4) lesson plan reflection of feminism issues in Cho Nam-Joo's novel Kim Ji Yeong, Born 1982 with a focus on the 2015–2016 setting using a constructivist approach.